High N-Cadherin Protein Expression in Ovarian Cancer Predicts Poor Survival and Triggers Cell Invasion - Assidi, Mourad (Frontiers in Oncology, 2022)
Ovarian cancer (OC) is among the most lethal cancer among all gynaecological malignancies. Since most OC patients are diagnosed only at advanced stages mainly because of their imperceptible/ nonspecific symptoms, survival rates are low. Therefore, more molecular biomarkers are needed to achieve more effective molecular stratification for better prognostic and theranostic outcomes. The cadherin family, particularly N-cadherin (N-CAD; also known as CDH2), is critical for cell-cell adhesion and epithelial- mesenchymal transition (EMT) of cancer. N- CAD protein has also been shown to be overexpressed in many advanced carcinomas. The aim of this study was to investigate the expression patterns of N-CAD protein, determine their correlations with the clinicopathological features of OC patients, and evaluate its prognostic value and involvement in EMT and metastasis. Protein expression of N-CAD was studied in 117 formalin-fixed and paraffin-embedded (FFPE) blocks from patients diagnosed with OC using Tissue Microarray and immunohistochemistry techniques. The N-CAD protein was overexpressed in 58% of our OC cohort. Furthermore, its cytoplasmic overexpression was significantly correlated with tumor grade (p= 0.05), tumor subtype (p= 0.05), tumor necrosis (p= 0.01), and age at menarche (p= 0.002). Interestingly, Kaplan-Meier analysis showed a significant correlation of disease-free survival (DFS) with OC patients with cytoplasmic N-CAD overexpression (p< 0.03, log rank). Patients with high N-CAD expression have approximately twice the recurrence rate at 5-year follow-up. The results of this study demonstrate a poor prognostic role of N-CAD overexpression in OC, which is reflected in higher recurrence and death rates of OC and its molecular contribution to EMT and distant metastasis. Therefore, patients with overexpressed OC need to be monitored more frequently and closely. Further studies with larger patient cohorts are needed to validate these findings, demystify the role of N-CAD in OC pathophysiology, and further investigate its role as a potential therapeutic target.